Coexistence of GH-Producing Pituitary Macroadenoma and Meningioma in a Patient with Multiple Endocrine Neoplasia Type 1 with Hyperglycemia and Ketosis as First Clinical Sign - A. Herrero-Ruiz; H. S. Villanueva-Alvarado; J. J. Corrales-Hernández; C. Higueruela-Mínguez; J. Feito-Pérez; J. M. Recio-Cordova (Case Reports in Endocrinology)
We present the clinical case of a patient who was admitted with an onset of diabetes mellitus (DM) with associated ketosis and whose clinical, hormonal, and radiological evolution revealed the presence of primary hyperparathyroidism, pancreatic neuroendocrine tumor, and GH-producing pituitary macroadenoma in the context of multiple endocrine neoplasia type 1 (MEN1). DM is relatively common in cases of acromegaly, but it is not generally associated with ketosis. Simultaneously, the patient presented a meningioma, which is associated with pituitary macroadenoma only in extremely rare cases.